Produksi dan Karakterisasi Enzim Selulase Ekstrak Kasar dari Bakteri yang Diisolasi dari Limbah Rumput Laut - Isna Rahma Dini; Ifah Munifah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
Seaweed waste is a source of bacteria that can produce cellulase enzyme. PMP 0126w isolate is one collection isolate of BBP4BKP obtained from seaweed Glacilaria sp. waste from Pameungpeuk area, Garut, West Java. The aims of this research were to produce and characterize the cellulase enzyme. PMP 0126w isolate was a Gram-positive rod shape bacteria. The isolate had 0.8 cellulolytic index on Carboxymethyl Cellulose (CMC) agar medium. The highest cellulase activity obtained on the third day of fermentation time with a cellulase activity of 0,074 U/mL and specific activity of 0.092 U/mg. Optimum activity of the cellulase enzyme crude extract was pH 5 and 300C. The activity of the cellulase was increased by addition of 5 mM CaCl2 and 10 mM FeCl3 ions and decreased by the addition of 10 mM ZnCl2 ions. The cellulase with the highest activity of 0.237 U/mL was obtained from Glacilaria sp. seaweed waste treated with NaOH 6%. Keywords: cellulose, characterization, production, seaweed waste